Clinical Holistic Medicine: Psychodynamic Short-Time Therapy Complemented with Bodywork. A Clinical Follow-Up Study of 109 Patients - Søren Ventegodt; Suzette Thegler; Tove Andreasen; Flemming Struve; Lars Enevoldsen; Laila Bassaine; Margrethe Torp; Joav Merrick (The Scientific World Journal)
This is a study of 109 patients who attended the Research Clinic for Holistic Medicine in Copenhagen during the 2004–2006 period, grouped according to the symptoms they presented with. Every new patient was asked to answer a 10-question composite questionnaire containing QOL1, QOL5, and four questions on ability to function socially, ability to function sexually, ability to love, and ability to work, rated on a 5-point Likert scale, on initial contact and after 1–3 months, when the patient had received about five treatments, the patient was asked to complete the questionnaire again, and finally again after 1 year. All had been to their general practitioner first with their problems and 30% had been in psychological/psychiatric treatment before. The patients were treated with short-time psychodynamic therapy (less than 40 sessions) including bodywork when necessary. More than half the patients had a bad or very bad self-assessed mental health before treatment, but after treatment only 15% reported a bad or very bad mental health (p < 0.001). Most had a complex of mental, somatic, existential, and sexual problems. Of the patients, 69.72% did the retest after treatment. We conclude that clinical holistic medicine was able to help the majority of these patients, even when patients had not been sufficiently helped by drugs, psychiatry, or psychology before. We found that outcome of therapy was not connected with severity of initial condition, but probably with the former experience of treatment. If psychiatric or psychological treatment had already failed, the patients were more difficult to help. The Square Curve Paradigm was used to document a large, immediate and lasting effect of the therapy.